"No poverty" - Sustainable development goals in the light of Polish statistics and social policy activities - Karolina Palimąka; Gabriela Karaś (Financial Internet Quarterly, 2022)
The purpose of this research is to examine the poverty phenomenon indicators in Poland through the prism of sustainable development. The subject of poverty and its consequences is often omitted in the discussion of sustainable development, or simplified only to social issues, yet it is an important aspect of economic development and implementation of Sustainable Development Goals (SDGs). The study will cover the problem of poverty in Poland, together with the assessment of the potential of implementation of sustainable development goals in terms of poverty eradication, as well as the issue of the impact of social policy activities on SDGs (named as 'no poverty') and household finances, both closely related to the risk of poverty. To achieve the aim of the study the authors use statistical data describing the issues of poverty and changes in this area in the period between 2010 and 2020 (or the most up-to-date data available) based on data from the Central Statistical Office in Poland.
Keywords: D14; I30; I32; I39; Q01; Q56; 330; poverty; sustainable development; household finances